Analisis Kesulitan Mahasiswa dalam Memahami Konsep Hukum Newton - Diyana, Tsania Nur; Widyaningtyas, Febrina Siska (Experiment: Journal of Science Education, 2025)
Newton's laws are fundamental concepts in mechanics and serve as the foundation for various other topics in physics. However, mastering these concepts remains a challenge for university students. This study aims to analyze the difficulties experienced by students in understanding Newton's laws. The research method employed is descriptive quantitative, involving 35 first-year physics education students. The instrument used was the Force Concept Inventory (FCI), consisting of 30 multiple-choice questions with five answer options each. Data analysis was conducted by identifying items where students' posttest answer percentages were below 50%. Crosstabulation was used to observe shifts in students' answers from the pretest to the posttest, followed by descriptive analysis. The study revealed several difficulties encountered by students regarding Newton's laws, including challenges in understanding the concept of resultant velocity of moving objects, the distinction between velocity and acceleration (Newton’s Second Law), and Newton’s Third Law. These findings are based on the analysis of FCI items number 8, 13, and 26.